CORPORATE FINANCIAL VULNERABILITY AND TAX AGGRESSIVENESS:EVIDENCE FROM INDONESIAN CONSUMER FIRMS - Mardiana Lestari; Lin Oktris; Faith Njaramba; Zubir Azhar (Fakultas Ekonomi dan Bisnis Universitas Trisakti, 2025)
This study examines how financial distress, institutional ownership, and leverage influence tax avoidance practices in Indonesian non-cyclical consumer companies during 2019-2023. While prior research shows inconsistent findings regarding these relationships, limited evidence exists on how financial vulnerability shapes tax strategies in emerging markets, particularly during periods of economic uncertainty. Understanding these dynamics is crucial given Indonesia's persistent tax gap and the unique characteristics of the consumer sector, which maintains stable revenues despite varying financial health across firms. Using panel data from 36 non-cyclical consumer companies listed on the Indonesia Stock Exchange over five years (180 firm-year observations), we employ multiple regression analysis with the Effective Tax Rate as the dependent variable measuring tax avoidance. Financial distress is measured using the Altman Z-Score, institutional ownership by percentage of shares held by institutional investors, and leverage by debt-to-equity ratio. The analysis controls for firm size and profitability to ensure robust results. The findings reveal that financial distress has a significant negative effect on tax avoidance, indicating that financially distressed firms reduce aggressive tax practices to maintain stakeholder trust and avoid regulatory scrutiny. However, institutional ownership and leverage show no significant effect on tax avoidance in this context. These results contribute to agency theory by demonstrating that financial constraints moderate the traditional principal-agent conflict regarding tax strategies. The implications suggest that tax authorities should focus monitoring efforts on financially stable firms rather than distressed ones, while investors can use financial health indicators as signals of tax risk exposure in emerging market contexts.